The End of the Wooden Shop: Wanganui Architecture in the 1890s - Pettigrew, Wendy; Southcombe, Mark (Architectural History Aotearoa, 2007)
The 1890s was a decade of remarkable progress in Whanganui. The depression of the 1880s was over. The town became an important port and distribution centre with railway connections to Wellington and New Plymouth as well as wharves at Castlecliff and in town. Alexander Hatrick began his riverboat service on the river enabling tourists from all over the world to travel the "Rhine of New Zealand." The colonial town developed culturally. The Technical School of Design was established in 1892, the public museum opened a few years later and the library was extended. The local MP, John Ballance, was Premier until his death in 1893; his state funeral and that in 1898 of the Māori chief, Te Keepa Rangihiwinui, were defining moments in Whanganui’s history. A 40-year building boom began, starting with the replacement of old town centre premises dating from the 1860s and earlier. In 1890 there were two architects in town, but only one with recognized qualifications: Alfred Atkins, FRIBA. Having been in practice with Frederick de Jersey Clere in the 1880s, Atkins’ practice blossomed in the 1890s. He was architect to both the Education and Hospital Boards at a time of major commissions and advisor to the Borough Council. He designed the museum and a large warehouse and bond store for Sclanders of Nelson and organized the architectural competition for what is now known as The Royal Whanganui Opera House. This paper examines these and other buildings together with some "gentlemen’s residences" as examples of the Victorian architecture which characterizes Whanganui today. During the 1890s the Borough Council continued to grapple with the problem of fires in town. The arguments raged over the merits of building in wood versus brick. This paper looks at the evolution of the Council’s eventual designation in 1898 of a downtown "brick area" with bylaws requiring at least brick side walls on all new buildings. The era of building permits began and the erection of new brick walls heralded the end of the wooden shop. The brick buildings that followed changed the character of Whanganui’s townscape.